Teachers’ Strategies to Overcome Students’ Misbehavior in Learning EFL - Rahmat, Rahmat; Dollah, Syarifuddin; Nur, Sahril (Journal of Excellence in English Language Education, 2024)
This study aimed to know the types of students' misbehavior and teachers’ strategies to overcome students' misbehavior in learning EFL. Teachers' strategies as the independent variable and students' misbehaviors as the dependent variable. This study used a descriptive qualitative method. There were 3 English teachers at SMA Insan Cendikia Syech Yusuf as the subjects of this research. The data of the research was obtained by observation and interview. Based on the research findings, it can be concluded that the subjects faced various students’ misbehaviors. These misbehaviors were categorized into four categories (verbal interruption, off-task behavior, physical movement, and disrespect to the teacher). In overcoming those misbehaviors, the subjects had some strategies to overcome students' misbehaviors. These strategies were non-verbal intervention, verbal intervention, and logical consequence.